The Combination of Gardenia jasminoides, Boswellia serrata, Commiphora myrrha, Foeniculum vulgarae, and Daucus carota Essential Oil Blend Improved the Inflammatory and Clinical Status in Respiratory Tract Infection of COVID-19 Patients: A Multicentre, Randomized, Open-label, Controlled Trial - Lestari, Keri; Babikian, Haig; Kulsum, Iceu Dimas; Ferdian, Ferdy; Ismail, Efriadi; Sumalim, Yelsen; Setiawan, Setiawan; Santoso, Prayudi; Hartantri, Yovita; Arifin, Arief Riadi; Meiliana, Anna; Sormin, Ida Paulina; Sugiono, Erizal (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Essential oils (EO) are complex volatile, naturally synthesized compounds from aromatic plants. It considers as healthy, effective, and safe since they were coming from nature. Gardenia jasminoides, Boswellia serrata, Commiphora myrrha, Foeniculum vulgarae, and Daucus carota are known to have antimicrobials, antioxidants, antiinflammation properties against respiratory tract infection. However, despite its natural content, a safety profile needs to be observed. Therefore, in this study, EO blend (EOB) made from the combination of these 5 plants was assessed for its efficacy and safety for respiratory tract infection in human.METHODS: A multicentre, randomized, open-label, phase II controlled trial involving 80 hospitalized adults with COVID-19 was conducted. One group of subjects only received standard of care (SoC), while the other group receive SoC and EOB orally for 10 days.RESULTS: There were significant decrease in interleukin (IL)-6 level (p=0.016) and interferon (IFN)-γ level (p=0.012), as well as better respiratory rate (p=0.024) for the group receiving SoC and EOB compared to the group receiving SoC only. However, there was no significant differences in aspartate aminotransferase (AST), alanine aminotransferase (ALT), creatinine, and the corrected QT interval (QTc) prolongation value in both groups. All subjects with adverse effects were improved and recovered, and there were no serious adverse events found.CONCLUSION: The combination of G. jasminoides, B. serrata, C. myrrha, F. vulgarae, and D. carota EOB could improve the inflammatory and clinical status and safe to be used as adjuvant therapy for treating COVID-19 in adults.KEYWORDS: essential oils, COVID-19, inflammation, safety